Climate Change and Salinity Effects on Crops and Chemical Communication Between Plants and Plant Growth-Promoting Microorganisms Under Stress - Ullah, Asad; Bano, Asghari; Khan, Naeem (Frontiers in Sustainable Food Systems, 2021)
During the last two decades the world has experienced an abrupt change in climate. Both natural and artificial factors are climate change drivers, although the effect of natural factors are lesser than the anthropogenic drivers. These factors have changed the pattern of precipitation resulting in a rise in sea levels, changes in evapotranspiration, occurrence of flood overwintering of pathogens, increased resistance of pests and parasites, and reduced productivity of plants. Although excess CO2 promotes growth of C3 plants, high temperatures reduce the yield of important agricultural crops due to high evapotranspiration. These two factors have an impact on soil salinization and agriculture production, leading to the issue of water and food security. Farmers have adopted different strategies to cope with agriculture production in saline and saline sodic soil. Recently the inoculation of halotolerant plant growth promoting rhizobacteria (PGPR) in saline fields is an environmentally friendly and sustainable approach to overcome salinity and promote crop growth and yield in saline and saline sodic soil. These halotolerant bacteria synthesize certain metabolites which help crops in adopting a saline condition and promote their growth without any negative effects. There is a complex interkingdom signaling between host and microbes for mutual interaction, which is also influenced by environmental factors. For mutual survival, nature induces a strong positive relationship between host and microbes in the rhizosphere. Commercialization of such PGPR in the form of biofertilizers, biostimulants, and biopower are needed to build climate resilience in agriculture. The production of phytohormones, particularly auxins, have been demonstrated by PGPR, even the pathogenic bacteria and fungi which also modulate the endogenous level of auxins in plants, subsequently enhancing plant resistance to various stresses. The present review focuses on plant-microbe communication and elaborates on their role in plant tolerance under changing climatic conditions.